Use of L-carnitine in larval rearing of turbot (Scophthalmus maximus. L.): first results. - Fernández-Pato, Carlos; Martínez-Tapia, Concha (2012)
The effect that L-Carnitine has on the growth and survival when administered in the diet during the larva1 period has been studied for turbot (Scophtalmus maximus). Two experimental groups have been compared, one having been treated with L-carnitine from the beginning of alimentation until weaning, and the other being used as the control. The L-carnitine was administered through live prey (rotifers and artemia). At the end o£ the period growth, weight and length, have been compared using a t-Student test and significant differences are observed in weight (p<0.05) but not in length (p>0.05); survival rates also show significant differences (p=0.0000) with the Lee-Desu statistic, favouring the treated group. No